2013
DOI: 10.1177/1753465813481022
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of chronic lung disease in deployed military personnel

Abstract: Abstract:Military personnel are a unique group of individuals referred to the pulmonary physician for evaluation. Despite accession standards that limit entrance into the military for individuals with various pre-existing lung diseases, the most common disorders found in the general population such as asthma and chronic obstructive pulmonary disease remain frequently diagnosed. Military personnel generally tend to be a more physically fit population who are required to exercise on a regular basis and as such m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Despite the uncertainty in the medical literature, unexplained respiratory symptoms occurring in soldiers deployed to Southwest Asia has been well described. [1][2][3][4] It has also been recognised that landbased personnel deployed to countries in Southwest and Central Asia, such as Iraq, Afghanistan, Kuwait, Qatar and the United Arab Emirates, may have been exposed to harmful particulate matter and respiratory pollutants. 3 However, there has been a paucity of data defining the histological features behind these pulmonary symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the uncertainty in the medical literature, unexplained respiratory symptoms occurring in soldiers deployed to Southwest Asia has been well described. [1][2][3][4] It has also been recognised that landbased personnel deployed to countries in Southwest and Central Asia, such as Iraq, Afghanistan, Kuwait, Qatar and the United Arab Emirates, may have been exposed to harmful particulate matter and respiratory pollutants. 3 However, there has been a paucity of data defining the histological features behind these pulmonary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that soldiers deployed to Southwest Asia are at an increased risk of developing respiratory symptoms. [1][2][3][4][5][6] Confounding factors, such as predeployment exposures and undiagnosed pulmonary conditions, contribute to the difficulty in exploring this association. [6][7][8] The correlation of deployment to Southwest Asia with chronic lung disease continues to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Although military personnel may be uniquely vulnerable and susceptible to airborne hazards, 6 a causal relationship between deploymentrelated exposures and respiratory disease has not been established in recent combat veterans. Despite several reviews, 3,6-8 recommendations, 3,9,10 and the launch of a national registry database, 11 few studies are available that document objective pulmonary function among veterans who had deployed to Southwest Asia. [12][13][14] At present, the literature is composed predominantly of retrospective studies and surveys, which have recently been reviewed elsewhere.…”
mentioning
confidence: 98%
“…Despite studies reporting that the BP practice do not constitute an elevated risk for human health, this conclusion is still heavily debated, mostly because toxicological, epidemiological and clinical data are not yet adequate to reliably evaluate the prevalence or severity of adverse effects of inhalational exposures to BP exhausts in military personnel. 34,35 …”
mentioning
confidence: 99%